A Case of Dyspnea in Pancreatic cancer Treated through Herbal Acupunture Treatment - Park Sang-Eun; Seo Sang-Ho; Hong Su-hyun; Kim Jae-Yeon; Shin Won-Tak; Youn Hyoun-Min; Hong Sang-Hoon (Korean Pharmacopuncture Institute, 2006)
Objective : This study planed to evaluate effect of oriental medicine therapy treatment method of dyspnea that happen from cancer of the pancreas patient who accompany Multiple metasis Methods : Patient complained dyspnoea during admission into dept . Of internal medicine, college of oriental medicine, Dong-eui Univ ,was appealed patient treated by Oriental medicine therapy that is of use Herb Medication and Herbal -acupuncture Treatment being diagnosed in lung asthenia including deficiency of Eum and insufficiency of Gi of the lung(폐허(肺虛)), the fire due to deficiency(허화(虛火)), and loving warfare of symptoms evaluated through VAS (visual analog scales). Results & Conclusion : Patient's difficulty in breathing symptoms took a favorable turn after treatment. This study means that Oriental medicine therapy that is difficulty in breathing symptoms that happen from patient surely has effectiveness.